Bringing the client back in: A comparison between political rationality and the experiences of the unemployed - Danneris, Sophie; Herup Nielsen, Mathias (Social policy & administration, 2018)
Categorizing the job readiness of unemployed clients is a task of the utmost importance for active labor market policies. Scholarly attention on the topic has mostly focused either on questions of political legitimacy or on how categories are practically negotiated in meetings between the welfare system and the client. This article proposes a comparative methodology, in which the political rationality of job readiness is contrasted with findings from a qualitative longitudinal study into the lived experience of recent welfare reforms. A group of 25 vulnerable Danish unemployed welfare claimants were interviewed repeatedly from 2013 to 2015 in the qualitative longitudinal study, and their accounts were compared to the political rationality on job readiness. Our analysis presents four striking areas of discrepancy between political rationality, on the one hand, and the logic of job readiness found in the vast amount of qualitative material, on the other hand. It is concluded that the specific comparative perspective is fruitful because: (i) it critically addresses the gap between the experiences of some unemployed people and the political rationality; and (ii) it adds the perspective of the targeted individuals themselves to the analysis of political categorization, thereby avoiding the well‐known risk of reducing welfare clients to mere manipulable objects.